2022
DOI: 10.1007/s00117-022-01051-1
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning in neuroimaging: from research to clinical practice

Abstract: Neuroimaging is critical in clinical care and research, enabling us to investigate the brain in health and disease. There is a complex link between the brain’s morphological structure, physiological architecture, and the corresponding imaging characteristics. The shape, function, and relationships between various brain areas change during development and throughout life, disease, and recovery. Like few other areas, neuroimaging benefits from advanced analysis techniques to fully exploit imaging data for studyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 105 publications
0
1
0
Order By: Relevance
“…Artificial intelligence (AI) plays a fundamental role in the interpretation and processing of data from fMRI, providing sophisticated tools to analyze in depth the functioning of the human brain [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. One high-impact area is advanced data analytics, where AI can identify complex patterns and correlations that would be difficult or impossible to identify manually [13,17,22].…”
Section: Integrating Fmri and Ai For The Brain Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Artificial intelligence (AI) plays a fundamental role in the interpretation and processing of data from fMRI, providing sophisticated tools to analyze in depth the functioning of the human brain [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. One high-impact area is advanced data analytics, where AI can identify complex patterns and correlations that would be difficult or impossible to identify manually [13,17,22].…”
Section: Integrating Fmri and Ai For The Brain Studymentioning
confidence: 99%
“…This means that AI can help reveal subtle relationships between brain activity and certain stimuli or conditions, leading to a deeper understanding of cognitive and neural functions [16,20]. Furthermore, AI is essential for automating critical processes such as brain segmentation and mapping of brain regions [14,15]. This automation significantly speeds up the analysis process and ensures greater accuracy, allowing scientists to focus more on interpreting results rather than manipulating raw data [18,19,21].…”
Section: Integrating Fmri and Ai For The Brain Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, these models prove to be valuable in detection tasks, identifying regions of interest (ROI) within images or patterns within sequences. The segmentation of data is another field where ML showcases its efficacy, along with many other contexts [15,22]. Their application also seems to have been embedded in many neurological disciplines, including epilepsy, movement disorders, neuropsychiatric diseases, etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, these differences might not be valid for some individual cases due to huge variability across participants. At this point, the combination of neuroimaging approaches and ML techniques plays an important role in providing us some answers related to individual diagnoses rather than populations (Nenning & Langs, 2022). Previous reviews that cover a combination of ML techniques for the prediction of several diseases by using EEG (Craik et al, 2019), fMRI (de Filippis et al, 2019; Nakano et al, 2020) and PET (Duffy et al, 2019) showed that neuroimaging techniques and ML might have a future on individual diagnostic decisions.…”
Section: Introductionmentioning
confidence: 99%